Collaboration Education Challenges and Optimizing MBKM Law Faculty Surabaya State University - Christian Felix Lumbanraja; Rafif Athaullah Gazali; Rafi Satrya Arvitto; Fadly Ady Nugroho (CV. Era Digital Nusantara, 2025)
The implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program in legal education presents both opportunities and challenges in fostering effective collaboration among students, faculty, and external institutions. This study aims to explore the challenges faced in the implementation of MBKM at the Faculty of Law, Surabaya State University, and to identify strategic approaches to optimize its effectiveness. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with faculty members, students, and program coordinators, as well as document analysis related to MBKM policies. The sample was determined using purposive sampling to ensure the inclusion of key stakeholders directly involved in MBKM activities. Data analysis was conducted using thematic analysis to identify patterns and key themes. The findings reveal that challenges include administrative inefficiencies, lack of coordination among stakeholders, and variations in student readiness. However, strategic interventions such as structured mentorship, digital integration, and policy alignment with academic requirements can enhance collaboration and program outcomes. This study contributes to the existing literature by providing a focused examination of MBKM’s implementation in legal education, highlighting the need for a more adaptive and structured approach. The implications of this research emphasize the necessity for universities to refine their MBKM frameworks to better support interdisciplinary learning and professional development.